A Rac Homolog Is Required for Induction of Hyphal Growth in the Dimorphic Yeast Yarrowia lipolytica - Hurtado, Cleofe A. R. (American Society for Microbiology, 2000)
Dimorphism in fungi is believed to constitute a mechanism of response to adverse conditions and represents an important attribute for the development of virulence by a number of pathogenic fungal species. We have isolated YlRAC1, a gene encoding a 192-amino-acid protein that is essential for hyphal growth in the dimorphic yeast Yarrowia lipolytica and which represents the first Rac homolog described for fungi. YlRAC1 is not an essential gene, and its deletion does not affect the ability to mate or impair actin polarization in Y. lipolytica. However, strains lacking functional YlRAC1 show alterations in cell morphology, suggesting that the function of YlRAC1 may be related to some aspect of the polarization of cell growth. Northern blot analysis showed that transcription of YlRAC1 increases steadily during the yeast-to-hypha transition, while Southern blot analysis of genomic DNA suggested the presence of several RAC family members in Y. lipolytica. Interestingly, strains lacking functional YlRAC1 are still able to grow as the pseudohyphal form and to invade agar, thus pointing to a function for YlRAC1 downstream of MHY1, a previously isolated gene encoding a C(2)H(2)-type zinc finger protein with the ability to bind putative stress response elements and whose activity is essential for both hyphal and pseudohyphal growth in Y. lipolytica.